Effect of heat treatment on tensile and fatigue deformation behavior of extruded Al-12 wt%Si alloy - Ham, Gi-Su; Baek, Min-Seok; Kim, Jong-Ho; Lee, Si-Woo; Lee, Kee-Ahn (Metals and materials international, 2017)
This study investigated the effect of heat treatment on tensile and high-cycle fatigue deformation behavior of extruded Al-12 wt%Si alloy. The material used in this study was extruded at a ratio of 17.7: 1 through extrusion process. To identify the effects of heat treatment, T6 heat treatment (515 °C/1 h, water quenching, and then 175 °C/10 h) was performed. Microstructural observation identified Si phases aligned in the extrusion direction in both extruded alloy (F) and heat treated alloy (T6). The average grain size of F alloy was 8.15 °C, and that of T6 alloy was 8.22 °C. Both alloys were composed of Al matrix, Si, Al 2 Cu, Al 3 Ni and AlFeSi phases. As T6 heat treatment was applied, Al 2 Cu phases became more finely and evenly distributed. Tensile results confirmed that yield strength increased from 119.0 MPa to 329.0 MPa, ultimate tensile strength increased from 226.8 MPa to 391.4 MPa, and the elongation decreased from 16.1% to 5.0% as T6 heat treatment was applied. High-cycle fatigue results represented F alloy’s fatigue limit as 185 MPa and T6 alloy’s fatigue limit as 275 MPa, indicating that high-cycle fatigue properties increased significantly as heat treatment was conducted. Through tensile and fatigue fracture surface analysis, this study considered the deformation behaviors of extruded and heat treated Al-Si alloys in relation to their microstructures.